Risk Factors and Patient-Reported Outcomes in Chinese Women with Postpartum Diastasis Recti Abdominis: An Observational Study - Zhu Y; Jiang L; Ye T; Liu Y; Sun L; Xiao L; Chen J; Wang T; Ren Y; Xu H; Zhao H; Mao X; et al. (Dove Medical Press, 2024)
Ying Zhu,1 Liyuan Jiang,2 Tiantian Ye,3 Yan Liu,4 Li Sun,2 Lijuan Xiao,5 Jiayu Chen,6 Ting Wang,7 Yinghua Ren,8 Hongjun Xu,8 Huihui Zhao,8 Xiaozhen Mao,8 Tiantian Shen9 1School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 2Department of Acupuncture and Rehabilitation, Hangzhou Hospital of Traditional Chinese Medicine, Hangzhou, 310005, People's Republic of China; 3The 1st Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 4The 2nd Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 5Department of Rehabilitation, Chun'an County Hospital of Traditional Chinese Medicine, Chun'an, 311799, People's Republic of China; 6Department of Rehabilitation, Huzhou Central Hospital, Huzhou, 313099, People's Republic of China; 7The 3rd Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 8Department of Acupuncture and Tuina, Community Health Service Center of Zhuantang Street, Hangzhou, 310024, People's Republic of China; 9Department of Acupuncture and Rehabilitation, Shengzhou Municipal Hospital of Traditional Chinese Medicine, Hangzhou, 312499, People's Republic of ChinaCorrespondence: Liyuan Jiang, Department of Acupuncture and Rehabilitation, Hangzhou Hospital of Traditional Chinese Medicine, No. 453, Stadium Road, Xihu District, Hangzhou, 310005, People's Republic of China, Tel +86-13018976755, Email Jiangliyuan520j@163.comPurpose: Diastasis recti abdominis (DRA) is a condition in which the linea alba is stretched and widened, and the abdominal muscles are separated from each other. DRA typically occurs in pregnant and postpartum women. We aimed to determine the risk factors and patient-reported outcomes (PROs) of DRA in Chinese postpartum women.Methods: This observational study was conducted in Hangzhou Hospital of Traditional Chinese Medicine, and involved 534 women who filled out the following risk-factor and PRO questionnaires: SF-MPQ-2, SF-ICIQ, LDQ, EPDS, MBIS, HerQles, and SF-36 (all Chinese versions). The inter-recti distance was measured by palpation. Statistical analyses were performed using SPSS v25.0 software and the Mann-Whitney U-test, chi-square test, binary logistic regression analysis (for risk factors of DRA), and the Kendall and Spearman tests (for correlation analysis).Results: After childbirth, 78.1% (417/534) of the enrolled women had DRA. Abdominal surgery (P = 0.002), number of pregnancies (P = 0.035), parity (P = 0.012), number of births (P = 0.02), fetal birth weight (P = 0.014), and waist-to-hip ratio in the supine position (P = 0.045) significantly differed between the DRA and non-DRA groups. Caesarean delivery was an independent risk factor for DRA. The PROs were significantly worse in the DRA group than in the non-DRA group.Conclusion: Caesarean delivery was an independent risk factor for DRA. Women with DRA are more likely to have limited physical activity or function after childbirth, lower self-confidence, and a decreased quality of life.Keywords: risk factors, patient-reported outcome measures, diastasis recti abdominis, postpartum period